Biocompatibility of MgF2-coated MgNd2 specimens in contact with mucosa of the nasal sinus – A long term study. (May 2015) - Weber, Constantin M.; Eifler, Rainer; Seitz, Jan-Marten; Maier, Hans J.; Reifenrath, Janin; Lenarz, Thomas; Durisin, Martin
Graphical abstract: Abstract: Up to now, different surgical techniques and stent systems have already been developed and tested for the continuous and adequate ventilation of the frontal sinuses. However, the results achieved still remain poor. Magnesium-based implants have been successfully used in numerous clinical applications. Offering excellent biocompatibility and biodegradability it may be the ideal material for the development of novel implants of the nasal sinus. Here, we present for the first time results on the behaviour of magnesium alloy in a unique environment, i.e. in contact to the nasal mucosa, air and nasal secretion. In a prospective longitudinal study, magnesium fluoride-coated MgNd2 specimens were implanted in the frontal sinuses of 12 minipigs for the investigation of biocompatibility and of the interface between the implant and the mucosa. Endoscopic examinations, histopathological evaluation and EDX measurements were performed regularly up to 180 days. Endoscopic evaluation showed focal mucosal reaction, however, without affecting the patency of the sinus. In addition, no signs of bacterial infections were observed. The EDX analyses showed a marginal but steady increase in the Mg concentration in the mucosa over 180 days. Histological analysis revealed a locally confined moderate mucosal hyperplasia and unspecific inflammatory reaction. Furthermore, we did not find any osteoinductive effects of the magnesium alloy. The results indicate the excellent biocompatibility of the MgNd2 alloy in contact with nasal mucosa and provide a novel material compound and solid proof-of-principle for the development of magnesium-based nasal stents.